2019
DOI: 10.35118/apjmbb.2019.027.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and characterization of medically and veterinary important flies of Bangladesh based on mitochondrial COI gene sequences

Abstract: Flies are considered serious pests which cause health problems of human and animal, transmitting many pathogenic microbes. Pest management programs depend on proper identification of pests. The present research work is an initiative to identify the medically and veterinary important flies based on mitochondrial COI gene sequences. Eleven species of the fly pests were identified. Among them, four fly species were the first record from Bangladesh. The phylogenetic analysis of retrieved sequences confirmed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The COI gene of all the specimens exhibited a high proportion of AT nucleotides, which was in agreement with previous findings made in Coleoptera and other insects (Simon et al 1994, Daniel 1999, Bajpai and Tewari 2010, Zhuang et al 2011, Zhang et al 2007, Aslam et al 2019aand 2019b, Rain et al 2019. This was caused by A-T bond, which has a noncoding region that has faster evolution rate compared to the coding region.…”
Section: Sequence Results and Blast Analysissupporting
confidence: 90%
“…The COI gene of all the specimens exhibited a high proportion of AT nucleotides, which was in agreement with previous findings made in Coleoptera and other insects (Simon et al 1994, Daniel 1999, Bajpai and Tewari 2010, Zhuang et al 2011, Zhang et al 2007, Aslam et al 2019aand 2019b, Rain et al 2019. This was caused by A-T bond, which has a noncoding region that has faster evolution rate compared to the coding region.…”
Section: Sequence Results and Blast Analysissupporting
confidence: 90%
“…Numerous researchers have recently explored the molecular identification of the American cockroach through the COI gene, including [35] who conducted a study in Saudi Arabia where they observed that the universal primer (LCO 1490 and HCO 2198) produced a single band with a size range of 700-800 bp when examined with 1% agarose gel electrophoresis. [12] Identified P. americana for the first time in Bangladesh based on COI gene sequences. Hashemi-Aghdam et al [15] stated that their PCR amplification generated a single 710 bp-sized amplicon for American cockroaches using a universal primer (LCO 1490 and HCO 2198) and also showed a significant intra-species variation within their populations.…”
Section: Discussionmentioning
confidence: 99%
“…The insect MT-DNA is a double-stranded molecule that varies in size from 14,503 bp to 19,517 bp [10]. Certainly, they are one of the most informative markers in phylogenetics [11] and have been projected as a systematic taxonomy and evolutionary research tool for species identification [12]. Consequently, these properties make it useful for regular PCR amplification and molecular marker application for lower-level problems [13].…”
Section: Introductionmentioning
confidence: 99%
“…For genomic DNA extraction, the leg or wing tissue samples were taken and used Wizard ® Genomic DNA Purification Kit, USA, following the manufacturer's protocol after little modification as narrated in Aslam et al (2019aAslam et al ( , 2019b and Rain et al (2019). The yield and integrity of DNA was measured using NanoDrop™ 2000 spectrophotometer (Thermo Fisher Scientific, USA) which was extracted from the samples.…”
Section: Dna Extractionmentioning
confidence: 99%